Fabrication and Characterization of Dye-Sensitized Solar Cells for Greenhouse Application - Jeum-Jong Kim; Mangu Kang; Ock Keum Kwak; Yong-Jin Yoon; Kil Sik Min; Moo-Jung Chu (International Journal of Photoenergy)
We have developed dye-sensitized solar cells using novel sensitizers with enhanced transmittance of red (625–675 nm) and blue (425–475 nm) wavebands to control the illumination condition in the greenhouse. Novel ruthenium bipyridyl sensitizers with general formulas (Me3PhN)4[Ru(dcbpy)2(NCS)2] (JJ-7) and (Me3BnN)4[Ru(dcbpy)2(NCS)2] (JJ-9) have been synthesized and demonstrated as efficient sensitizers in dye-sensitized solar cells for greenhouse application. Under standard AM 1.5 sunlight, the solar cell of JJ-7 using a liquid-based electrolyte exhibits a short-circuit photocurrent density of 8.49 mA/cm2, an open-circuit voltage of 0.83 V, and a fill factor of 0.71, corresponding to an overall conversion efficiency of 4.96% on 5 μm TiO2 film. The transmittance of JJ-7 and JJ-9 shows 62.0% and 61.0% at 660 nm and 18.0% and 15.0% at 440 nm for cultivation on 5 μm TiO2 film, respectively.